Standardising Fatherhood across Cultures: A Linguistic Approach to Studying the Communication of a New Global Company Policy in Multinational Corporations - Bamford, Agnes Marie (HERMES - Journal of Language and Communication in Business, 2022)
A current trend in multinational corporations (MNCs) is a strong focus on diversity management in order to attract and retain talent. The present study investigates the linguistic manifestation and justification of a very recent company policy intended to facilitate this trend, viz., global paternity leave. The study aims to contribute to the linguistic turn in organisational studies. As a theoretical point of departure, Corporate Communication, and specifically links between Corporate Social Responsibility (CSR) and Diversity Management communication are discussed. Concepts and tools from text linguistics are then applied to investigate the communication strategies employed when introducing the new family leave policy in four MNCs headquartered in the UK and Norway, respectively. The material consists of a set of texts on global parental leave produced by the four companies. The linguistic analysis identifies similarities as well as differences between the British and Norwegian companies in how the new global leave policy is presented. The findings also demonstrate a tension between focussing on the CSR efforts gender equality and inclusion in the justification of the new measure intended to support the MNCs’ diversity management efforts.